Dinamika Kinerja Penyaluran ZISWAF Antar provinsi di Indonesia: Analisis Discrete-Time Markov Chain Berbasis Python - Aninta Gina Sharfina; Arta Amaliah Nur Afifah; Andi Agusti Ahmad Kurniawan; Aulia Lestari; Andi Nur Pratiwi Fatmala; Nur Hayatiningsih (STIKes Ibnu Sina Ajibarang, 2026)
The effectiveness of Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) management depends not only on the amount of funds collected but also on the sustainability of their distribution performance across regions. However, previous studies have primarily employed static approaches, providing limited evidence on how distribution performance changes over time. This study aims to analyze the dynamics of ZISWAF distribution across Indonesian provinces using a Discrete-Time Markov Chain approach. The study uses panel data from 34 provinces during 2019–2023 obtained from the National Board of Zakat (BAZNAS). The analysis includes the Transition Probability Matrix, Persistence Rate, Steady-State Probability, Mobility Index, Expected Duration, and a robustness check. The findings indicate that ZISWAF distribution is characterized by high stability, with the highest persistence observed in the high-distribution category. Transitions occur mainly between adjacent categories, while direct movement between low and high categories is absent, indicating a gradual improvement process. In the long run, the system is projected to converge toward the high-distribution category. These findings provide empirical evidence that provincial distribution performance is relatively stable and evolves incrementally. The study contributes to the literature by applying a dynamic approach to evaluate ZISWAF distribution and offers evidence-based insights for strengthening institutional capacity, governance, and distribution strategies across provinces